The man can - Coan, Sharon (Huntington Beach, CA : Teacher Created Materials, 2012)
A man goes shopping for soup to eat.
Cover title.
"-an"--Back cover.
"TCM 13926"--Back cover.
School Library Journal, April 2012
0.8
Preschool
Keywords: Food habits -- Juvenile fiction; Eating customs -- Fiction; Eating customs -- Fiction; Readers (Publications)